2018
DOI: 10.1002/jlb.3vma0118-035r
|View full text |Cite
|
Sign up to set email alerts
|

Extension and refinement of the recognition motif for Toll-like receptor 5 activation by flagellin

Abstract: TLRs sense conserved and essential molecular components of microbes that invade multicellular organisms. The wide range of TLR agonists, differing in size and shape, is recognized either through a single or a pair of binding sites on the ectodomains of TLRs. TLR5 recognizes bacterial flagellin through two distinct binding sites on the ectodomain, the first facilitating primary binding of flagellin and the second guiding receptor dimerization necessary for signaling. The regions of flagellin recognized by TLR5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…The consensus sites for TLR5 recognition in the flagellin FliC are localized at stacking sites between the flagellin monomers and therefore are not accessible when the filament is formed. Hence, when polymerized, the interaction domain of FliC with TLR5 is masked, therefore whole flagella do not signal through TLR5, which occurs only when FliC is monomeric ( 41 , 50 , 51 ). Intact purified periplasmic flagella from Treponema denticola were not able to activate TLR5 as well ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consensus sites for TLR5 recognition in the flagellin FliC are localized at stacking sites between the flagellin monomers and therefore are not accessible when the filament is formed. Hence, when polymerized, the interaction domain of FliC with TLR5 is masked, therefore whole flagella do not signal through TLR5, which occurs only when FliC is monomeric ( 41 , 50 , 51 ). Intact purified periplasmic flagella from Treponema denticola were not able to activate TLR5 as well ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial flagellar filaments also play a critical role in innate immunity in βand γ-proteobacteria (Hayashi et al, 2001;Andersen-Nissen et al, 2005). In addition to the D1 domain, the D0 domain is required for full TLR5 activation (Yoon et al, 2012;Song et al, 2017;Ivičak-Kocjan et al, 2018). However, βand ε-proteobacteria are able to evade the TLR5 activation (Andersen-Nissen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In gram-negative βand γ-proteobacteria, FliC also serves as a pathogen-associated molecular pattern that is recognized by Toll-like receptors (TLRs) on host innate immune cells (Hayashi et al, 2001;Andersen-Nissen et al, 2005;Song et al, 2017). The interaction between the D1 domain of FliC and the ectodomain of TLR5 was determined (Yoon et al, 2012;Song et al, 2017;Ivičak-Kocjan et al, 2018). Recent mutagenesis studies reported that the D0 domain also contributes to TRL5 activation (Forstnerič et al, 2017;Song et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, flagellins are usually species-specific ( 27 ), and there are significant differences in the immune properties of flagellins from different bacterial sources ( 28 ). Even from the same bacteria, the immunogenicities of different flagellins can differ markedly ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to variation in the sequences and domains of flagellins, flagellins from diverse bacterial species use different TLR5 recognition mechanisms ( 34 ). For activation, the receptor must undergo a ligand-induced conformational change ( 27 ). In the present study, we aimed to identify the specific ligand-binding sites on the surface of ligand-receptor complexes.…”
Section: Discussionmentioning
confidence: 99%